The Relationship between Family Emotional Support, Psychological Capital, Female Job Satisfaction and Turnover Intention - Ganji, Seyedeh Fatemeh Ghasempour; Johnson, Lester W. (International Journal of Economics, Business and Management Studies, 2020)
In developing countries, the role of women in miscellaneous occupations has kept its importance over the decades. So, it seems necessary to examine factors that may affect female job response. The purpose of this study was to investigate the effect of family emotional social support on both job satisfaction and turnover intention, as well as examine the moderating role of psychological capital, namely, hope, optimism, self-efficacy and resilience as an internal factor. Using a self-report questionnaire, a sample of 210 female respondents was selected. Data was analyzed using confirmatory factor analysis and PLS structural equation modeling. The results indicated that family emotional support affected both job satisfaction and turnover intention positively. The partial mediating role of psychological capital in the relationship between family emotional social support and job satisfaction was supported. This research considers the role of family emotional support and psychological capital on female employee job satisfaction and turnover intention. This research provides in-depth knowledge about the role of females in Iranian employment culture.